Remote sensing of wetland types: Subtropical wetlands of southern hemisphere - Costa, Maycira; Evans, Teresa; Silva, Thiago S.F. [UNESP] (Springer Nature, 2018)
The Pantanal is a large cross-border wetland system in South America that supports a diversity of ecosystems. This internationally important wetland is under threat from water diversion but also agricultural development and there is a need for satellite-based observations to characterize, map, and monitor the changing extents and states of the wetlands. To achieve this, a number of connected studies have been undertaken using combination of Synthetic Aperture Radar (SAR) operating at C- and L-band. Different lake types were also classified using an object-oriented approach, with these linked to different levels of salinity, primarily through association with vegetation types.
Keywords: Lake types; Synthetic aperture radar; Vegetation; Wetlands